Upaya Peningkatan Pengetahuan Mobilisasi Ibu Post Sectio Caesarea Di Rsu Assalam Gemolong - Markhamah, Faridah Miftakhul; , Sulastri, S.Kp., M.Kes (2016)
Maternal and Newborn Health care is one of the key elements in determining the health status of communities can be measured from the Maternal Mortality Rate (MMR). Venous thromboembolism and pulmonary embolism (PE) in pregnancy is a major cause of maternal mortality and morbidity. The incidence of pulmonary embolism in the United States to be the cause of maternal deaths exceed infection, hemorrhage and preeclampsia. It happened> 500,000 every year and causes 200,000 deaths. By doing ambulation / early mobilization can prevent complications such as pulmonary embolism and deep vein thrombosis. Factors that play an important role in realizing the implementation of early mobilization is the level of knowledge. If someone lower level of knowledge of the benefits and goals of mobilization it will greatly affect the level of implementation. Objective: To increase knowledge about the mobilization of post sectio caesarea and implement early mobilization in patients post sectio caesarea appropriate nursing standards. Methods: This study used a descriptive method by collecting data, analyzing the data, and draw conclusions. Results: After 3 days of nursing actions during the early mobilization patients were able to implement gradually.